Amnion-Derived Mesenchymal Stem Cell Exosomes-Mediated Autophagy Promotes the Survival of Trophoblasts Under Hypoxia Through mTOR Pathway by the Downregulation of EZH2 - Chu, Yijing; Chen, Weiping; Peng, Wei; Liu, Yong; Xu, Lin; Zuo, Jianxin; Zhou, Jun; Zhang, Yan; Zhang, Ning; Li, Jing; Liu, Ling; Yao, Ke; et al. (Frontiers in Cell and Developmental Biology, 2020)
Human amniotic mesenchymal stem cells (AD-MSCs) have been reported as a promising effective treatment to repair tissue. Trophoblast dysfunction during pregnancy is significantly involved in the pathogenesis of preeclampsia (PE). To understand how AD-MSCs regulated trophoblast function, we treated trophoblasts with AD-MSC-derived exosomes under hypoxic conditions. The treatment markedly enhanced the trophoblast proliferation and autophagy. Furthermore, significant decrease of EZH2 expression and inactivation of mTOR signaling were observed in AD-MSC exosomes-treated trophoblasts. Consistent with these findings, overexpression of EZH2 activated the mTOR signaling in trophoblasts, and reduced the autophagy and survival of trophoblasts, even in the presence of AD-MSC-derived exosomes. In addition, EZH2 inhibition exhibited the same trophoblast autophagy-promoting effect as induced by AD-MSC-derived exosomes, also accompanied by the inactivation of mTOR signaling. Importantly, when EZH2 was overexpressed in trophoblasts treated with PQR620, a specific mTOR signaling inhibitor, the autophagy and proliferation in trophoblasts were decreased. Studies on human placental explants also confirmed our findings by showing that the expression levels of EZH2 and mTOR were decreased while the autophagy-associated protein level was increased by AD-MSC-derived exosome treatment. In summary, our results suggest that EZH2-dependent mTOR signaling inactivation mediated by AD-MSC-derived exosomes is a prerequisite for autophagy augmentation in hypoxic trophoblasts.